PENDAMPINGAN IMPLEMENTASI DIGITAL MARKETING PADA UMKM GAPOKTAN MANDIRI JAYA DI DESA CIKARAWANG - Ayumi Fitriani Gunawan; Aisyah Ramdani Santoso; Atisah Raihan Fadillah; Aulia Raihan Fadillah; Thalla Syaikha Zakira (Jurnal Abdi Insani, 2023)
The widespread of Covid-19 has extensive repercussions, particularly on the economy and societal well-being. The Institute for Research and Community Engagement (LPPM) of IPB University, through the IPB Goes To Field (IGTF) Program, collaborates with the IPB Vocational School to contribute to the revival of Micro, Small, and Medium Enterprises (MSMEs) affected by pandemic. One of them is UMKM Gapoktan Mandiri Jaya. A substantial decline in sales has been experienced post-pandemic, particularly given the reliance on conventional sales methods involving face-to-face interactions and direct marketing. The IGTF program’s objective is to assist MSMEs in enhancing their sales by leveraging technological advancements, specifically through digital marketing. This initiative aims for business operator not only to acquire technical understanding but also to become proficient in autonomous operations after the program’s completion. The method employed in this undertaking is Participatory Learning Activity (PLA). Intensive mentoring will be provided to business operators during the knowledge dissemination process, culminating in operational simulations. The implementation of digital marketing guidance unfolds across various stages, beginning with awareness campaigns, followed by digital marketing planning, photo product session, digital marketing mentoring, and immersive simulation. Sustainable digital marketing provisions are delivered in two stages: writing pocket guidebook and provision of photos and videos resources.